Macrófitas aquáticas submersas: fotossíntese, crescimento e variáveis abióticas da água - Pezzato, Maura Maria (2007)
Cabomba furcata and Egeria najas are rooted submerged species of aquatic macrophytes that occurred in Oleo Lagoon (21° 36 S e 47° 49 W), Mogi-Guaçu river floodplain (Ecological Station of Jataí, Luiz Antônio, SP). Limnological characteristics of the water and the net photosynthesis of C. furcata were determined in Oleo lagoon at the rainy and the dry periods (summer and winter, respectively); aiming to evaluate the influence of abiotic variables on photosynthetic rates in situ. The dry season, the lagoon s water was highly transparent, conversely, at the rainy season, the water presented high amounts of suspended matter, which decreased the water transparency. In laboratory, experiments were performed with C. furcata and E. najas to verify the influence of pH and light on net photosynthetic. Besides, the effect of temperature on growth rates and net photosynthesis were analyzed for E. najas. Photosynthesis rates were determined by changes in dissolved oxygen concentration using the light and dark bottles technique (Winkler´s method). The growth rates were estimated by increment of biomass. The abiotic variables examined and the net photosynthesis of C. furcata presented clear seasonal pattern. C. furcata and E. najas were capable to use only free CO2 dissolved in the water. Both species showed adaptability to low intensities of light and perhaps considered shade species. Nevertheless, C. furcata presented lower values of Ks than E. najas (25 and 55 µmol m-2 s-1, respectively), probably because it is less tolerant to high light intensities. The optimal temperature for E. najas growth rate was 25 ºC; with generally higher biomass gain between 20 and 30 ºC. The largest values of net photosynthesis of E. najas were obtained to 25 ºC, independent of the temperature it was acclimated (15 - 30 ºC). The processes of photosynthesis and growth of E. najas presented low sensibility to the temperature increase (Q10 = 1.85 and 1.17, respectively).